On R#-Closed and R#-Open Maps in Topological Spaces - K, Raghavendra; M. Ittanagi, Basavaraj (International Journal of Engineering and Technology, 2018)
Defining and investigating properties of R#-closed maps, R#-open maps, R#*-closed maps and R#*-open maps in topological spaces.2010 Mathematics Classification: 54A05, 54A10Â